Heavy metals contamination in sediments and selected commercially important bivalves in Marudu Bay - Delta Jenetty Denil (2018)
Marudu Bay has become an important fishing ground due to its high marine biodiversity. Other than that, Kata Marudu district has been identified as potential area for agriculture apart from a holding potential for eco-tourism activities. However, the growing activities of agriculture (especially oil palm plantation) which involved the usage of chemicals (fertilizer, pesticides etc.) were blamed for the mass mortality of cultured green mussel in Tanjung Batu, Marudu bay. The mass mortality event was severely affected the green mussel aquaculture in the area. Hence, this study was conducted in order to measure the level of heavy metal in commercially important bivalves originating from Marudu bay and to investigate its relationship with the physicochemical variables. Other than that, this study also examine if the level of metals in the bivalves can possibly bring about health risk to consumers. Current study was conducted by collecting green mussel (n=120) and sediment (n=36) samples monthly for 12 months period. The samples were acid digested using hot block digestor in order to determine the heavy metal content. Principal component analysis (PCA) was done to highlight the relationship between variables ( environmental variables, heavy metals content in sediment and bivalves). For human health risk assessment, four species of bivalve (green mussel, pacific oyster, marsh clam and Asiatic hard clam) were collected and assessed for potential risk to human health due to heavy metal intoxication. It was found that, the heavy metal content in green mussel affected by season. However, some metal elements in sediment were not significantly different throughout the study period. Through the PCA, it was found that, heavy metals in the green mussel and sediment may have been contributed by anthropogenic sources (such as chemical residues, weathering processes and boating activities) in the bay. Moreover, pacific oyster (MPI=15.03) was the most heavy metal contaminated followed by green mussel (MPI=S.31), marsh clam (MPI=6.86) and Asiatic hard clam (MPI=S.79). The four species of bivalves were found to present health risk of heavy metal intoxication when consumed in excessive amount over a prolonged period.